دور محاسبة التكاليف في تحسين أداء المؤسسات الصحية بالجزائر - سبع, صبرينة (جامعة الوادي - University of Eloued, 2023)
تهدف هذه الورقة البحثية الى التعريف بنظام محاسبة التكاليف بصفة عامة، ونظام محاسبة التكاليف الصحية بصفة خاصة، حيث تطرقنا من خلالها الى معرفة اهمية واهداف محاسبة التكاليف، وكذلك وسائل مراقبة محاسبة التكاليف الصحية، التي بدورها تهدف الى تخفيض هذه الاخيرة، من خلال التقارير التي نتحصل عليها بعد تحليلها لمساعدة المسيرين في اتخاذ قرارات سليمة. وكما هو معلوم فان المؤسسات الصحية بالجزائر تعتمد على نظام المحاسبة العمومية، حيث يحتاج هذا القطاع لتبني نظام محاسبة التكاليف، ولمعرفة مدى تطبيق نظام محاسبة التكاليف بالمؤسسات الصحية بالجزائر ومساهمته في تحسين ادائها، قمنا بدراسة ميدانية من خلال توزيع استبانة على عينة تتكون من 60 فردا This research aims to introduce the cost accounting system in general, and the health cost accounting system in particular, through which we discussed the importance and objectives of cost accounting, as well as the monitoring methods of health cost accounting, which in turn aims to reduce costs, through the reports that we obtained after analyzing costs that helps managers in making correct decisions. As it is known, health institutions in Algeria depend on the public accounting system, as this sector needs to adopt a cost accounting system, and to know the extent to which the cost accounting system is applied in health institutions in Algeria and its contribution to improve their performance, We conducted a field study at the sector level by distributing a questionnaire to a sample consisting of 60 individuals, where it became clear to us the extent to which public health institutions in Algeria are interested in adopting the cost accounting system as it helps decision makers in making sound decisions.
The role of cost accouniting in improving the performance of health institutions in Algeria
مقال
Keywords: محاسبة التكاليف ; محاسبة التكاليف الصحية ; المؤسسات الصحية ; مراقبة التكاليف; cost accounting؛ health cost accounting؛ health institutions؛ cost control.